Penyuluhan pada Anak tentang Urgensi Menabung Sejak Dini dalam Upaya Penanaman Sikap Kewirausahaan - Nazmatul Khairat; Zailani Zailani (Community: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of implementing the real work leture is to help micro small and medium enterprises in Citaman Jernih village to manage finanes digitally by utilizing technology such as online book keeping application. the use off this online book keeping applicationc makes it easier for micro small and medium enterprises actor to generate financial report automatically. The results of the implementation of the real work lecture show that problems can be solved digitally in recording financial statemens, saving a lot time, and making it easier to record because it can be done anywhere and anytime.